The The Correlation Between Patient Satisfaction Regarding Nutrition Service And Hospital Length Of Stay With Food Waste In Covid–19 Patients - Budhi Setianto; Agus Aan Adriansyah; Umi Hanik; Difran Nobel Bistara (Jurnal Ilmiah Kesehatan, 2021)
Patient satisfaction is one indicator of the success of food delivery in the hospital. In the condition of the Covid-19 patient, there are several symptoms which will affect the length of stay in the hospital so that the patient’s nutrition greatly affects the patient’s improvement. This study aims to determine the relationship between food serving satisfaction and length of stay on leftover food in Covid-19 patients. This study used a quantitative method with observational and cross-sectional research method in the isolation room of RSI Surabaya in July-September. The data were processed using chi square test. The results showed that there was a relationship between the satisfaction of serving food and leftovers (P= 0,000), while the length of stay in Covid-19 patients had no relationship with food waste (P= 0,517). There is a relationship between the satisfaction of the patient’s food presentation and the food waste, this shows that the better the patient’s assessment of the assessment of the food presentation, the are no food waste. Meanwhile, the length of stay of patient in the Covid-19 isolation room did not have a relationship with food waste so that the length of stay did not affect the food waste.